Blockchain Technology: Can Data Security Change Higher Education Much Better? - Mulyati Mulyati; Ilamsyah Ilamsyah; Aris Aris; iketut gunawan; Muhammad Suzaki Zahran (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
Most college celebrities may not be very familiar with blockchain, except maybe for a few people who follow the financial cycle of a cryptocurrency called Bitcoin. Blockchain is a security technology that can replace traditional academic transcripts and provide a new model for sharing scientific information. This makes blockchain a useful learning tool or even as a medium for channeling or storing academic data. Apart from that, Blockchain can also be used to determine the ownership of a person's intellectual property. The proliferation of false credentials micro-credentials encourages academics to be able to strengthen the data security system implemented. Therefore, to strengthen and make it easier to validate the validity of these micro-credentials, this blockchain technology is considered very suitable to be used as a solution. Therefore, in this study the author uses the literature review method with the aim of finding out whether blockchain technology can update the Indonesian education system to a better domain or not.